PENGARUH PROMOSI TERHADAP KEPUTUSAN PEMBELIAN YAMAHA NMAX PADA PT YAMAHA BAHANA LAMPUNG - Desi Derina Yusda (LPPM UNIVERSITAS BINA INSAN, 2020)
This study aims to test and analyze the effect of promotion on purchasing decisions Yamaha Nmax at PT Yamaha Bahana Lampung. The population in this study were consumers who bought Yamaha Nmax at PT Yamaha Bahana Lampung from July to October 2020 with a total of 37 consumers. The sample used is the entire population because there are few respondents. Primary data collection using a questionnaire. The questionnaire was processed and tested for validity and reliability, after which the questionnaire was distributed to the research sample. This study uses simple linear regression. From the results of the test and analysis, promotion has a significant effect on the purchase decision of Yamaha Nmax at PT Yamaha Bahana Lampung by 59.8%, the remaining 40.2% is from variables or other factors not examined.